Studies in Plato's Metaphysics (RLE. - Allen, R. E. (Routledge library editions. Plato., 2012)
Did Plato abandon, or sharply modify, the Theory of Forms in later life? In the Phaedo, Symposium, and Republic it is generally agreed that Plato held that universals exist. But in Parmenides, he subjected that theory to criticism. If the criticism were valid, and Plato knew so, then the Parmenides marks a turning point in his thought. If, however, Plato became aware that there are radical differences in the logical behaviour of concepts, and the later dialogues are a record of his attempt to analyse those differences, then Plato's thought can be said to have moved in a new and vitally importa.